Работа с родителями в условиях лекотеки - Нурсеитова, С.Г. (My University, 2016)
The article is characterized by one of the main directions Lekoteka – providing psychological and educational assistance to support parents of children with development disorders. Presents the results of an experimental joint work employees kinder – garden, university teachers and students on the problem of psychology-pedagogical support for children not covered by preschool educational programs.
Keywords: accompaniment; cooperation; designing; training; seminar